Tanah Aset PT. Kereta Api Indonesia (PERSERO) Sebagai Jaminan Dengan Dibebani Hak Tanggungan - Wiyanti, Elisse Septiani; Pritiana , Deta Frischa; Larindo, Randy Hudan (Yuriska: Jurnal Ilmiah Hukum, 2021)
Background: Land assets belonging to PT. Kereta Api Indonesia (Persero) originating from grondkaart and converted based on the provisions in Law No. 5 of 1960 concerning basic rules of Agrarian Principals can be guaranteed by using dependent rights guarantee institutions. Law No. 5 of 1960 concerning the Basic Rules of Agrarian Trees has a mission to create unification of land ins and out arrangements, so in terms of guarantees must also be contained in a set. Research Metodes: The research method used is the statute approach. The type of legal material used is primary legal material and secondary legal material that is analyzed by studying the legal issues that occur. PT. Kereta Api Indonesia (Persero) has land assets derived from grondkaart. Findings: The creation of Law No. 4 of 1996 concerning The Right of Dependents on Land and Objects Related to Land aims so that there is no dualism in the guarantee institution for land objects. This is because Law No. 4 of 1996 concerning The Right of Dependents on Land And Objects Related to Land expressly determines the kind of land rights that can be used as collateral objects. The mention of Dependent Rights in the Basic Agrarian Law is prepared in lieu of hypocrisy and credietverband guarantee rights institutions. Conclusion: Management rights must be granted rights to other land on it that are cooperated with other parties in order to be burdened with dependent rights. Land rights that can be granted above the Management Rights are The Right to Build, Right of Use, or Property Rights.